REFLECTIONS ABOUT THE IMPACTS OF NATURAL AND TECHNOLOGICAL DISASTERS ON EUROPEAN HEALTH SYSTEMS - Cunha, Noémia Salgado (European Scientific Journal, ESJ, 2012)
﻿The present article aims to analyze the impact of natural and technological disasters in the European Union (EU) and in the European health systems. The strong impact of the economic and financial crisis, which has become more serious in the European countries, has made necessary for the member states to revise their budgets, and with this to rethink their policies of disaster prevention. Their occurrence lead, directly or indirectly, to implications in the health system budgets, given the huge number of people affected and deaths caused by these kinds of events. Regarding the prevention of two new calamities of modern times, the natural and the technological accidents, it is possible to notice that the action of the European health systems and of the Europeans’ Environmental, Health and Consumer Commission, is essentially based on action within the framework of epidemics, pollution related diseases, road accidents and injuries caused by high temperatures. It leaves out floods and storms, which are the ones that most affect the population of the 27 EU member states. These kinds of accidents concern the public health and should be treated as such.